Subtractive genomics and comparative metabolic pathways profiling revealed novel drug targets in Ureaplasma urealyticum - Chen, Liesong; Zhang, Zhuojia; Zeng, Qilin; Wang, Wei; Zhou, Hui; Wu, Yimou (Frontiers in Microbiology, 2024)
IntroductionUreaplasma urealyticum is a commensal organism found in the human lower genitourinary tract, which can cause urogenital infections and complications in susceptible individuals. The emergence of antibiotic resistance, coupled with the absence of vaccines, underscores the necessity for new drug targets to effectively treat U. urealyticum infections.MethodsWe employed a subtractive genomics approach combined with comparative metabolic pathway analysis to identify novel drug targets against U. urealyticum infection. The complete proteomes of 13 Ureaplasma strains were analyzed using various subtractive genomics methods to systematically identify unique proteins. Subsequently, the shortlisted proteins were selected for further structure-based studies.ResultsOur subtractive genomics analysis successfully narrowed down the proteomes of the 13 Ureaplasma strains to two target proteins, B5ZC96 and B5ZAH8. After further in-depth analyses, the results suggested that these two proteins may serve as novel therapeutic targets against U. urealyticum infection.DiscussionThe identification of B5ZC96 and B5ZAH8 as novel drug targets marked a significant advancement toward developing new therapeutic strategies against U. urealyticum infections. These proteins could serve as foundational elements for the development of lead drug candidates aimed at inhibiting their function, thereby mitigating the risk of drug-resistant infections. The potential to target these proteins without inducing side effects, owing to their specificity to U. urealyticum, positions them as promising candidates for further research and development. This study establishes a framework for targeted therapy against U. urealyticum, which could be particularly beneficial in the context of escalating antibiotic resistance.